Single-Cell Visualization Deep in Brain Structures by Gene Transfer - Sugiyama, Sayaka; Sugi, Junko; Iijima, Tomoya; Hou, Xubin (Frontiers in Neural Circuits, 2020)
A projection neuron targets multiple regions beyond the functional brain area. In order to map neuronal connectivity in a massive neural network, a means for visualizing the entire morphology of a single neuron is needed. Progress has facilitated single-neuron analysis in the cerebral cortex, but individual neurons in deep brain structures remain difficult to visualize. To this end, we developed an in vivo single-cell electroporation method for juvenile and adult brains that can be performed under a standard stereomicroscope. This technique involves rapid gene transfection and allows the visualization of dendritic and axonal morphologies of individual neurons located deep in brain structures. The transfection efficiency was enhanced by directly injecting the expression vector encoding green fluorescent protein into neurons instead of monitoring cell attachment to the electrode tip. We obtained similar transfection efficiencies in both young adult (≥P40) and juvenile mice (P21-30). By tracing the axons of thalamocortical neurons, we identified a specific subtype of neuron distinguished by its projection pattern. Additionally, transfected mOrange-tagged vesicle-associated membrane protein 2—a presynaptic protein—was strongly localized in terminal boutons of thalamocortical neurons. Thus, our in vivo single-cell gene transfer system offers rapid single-neuron analysis deep in brain. Our approach combines observation of neuronal morphology with functional analysis of genes of interest, which can be useful for monitoring changes in neuronal activity corresponding to specific behaviors in living animals.